The Laser-assisted photoelectric effect of He, Ne, Ar and Xe in intense extreme ultraviolet and infrared laser fields. Issue 4 (21st February 2016) - Hayden, P.; Dardis, J.; Hough, P.; Richardson, V.; Kennedy, E. T.; Costello, J. T.; Düsterer, S.; Redlin, H.; Feldhaus, J.; Li, W. B.; Cubaynes, D.; Meyer, M.
Abstract : In this paper, we report results on two-colour above-threshold ionisation, where extreme ultraviolet pulses of femtosecond duration were synchronised to intense infrared laser pulses of picosecond duration, in order to study the laser-assisted photoelectric effect of atomic helium, neon, krypton and xenon which leads to the appearance of characteristic sidebands in the photoelectron spectra. The observed trends are found to be well described by a simple model based on the soft-photon approximation, at least for the relatively low optical intensities of up to 5 × 10 11 W c m - 2 employed in these early experiments.